The role of vision in Parkinson's disease locomotion control: Free walking task - Vitorio, Rodrigo [UNESP]; Lirani-Silva, Ellen; Barbieri, Fabio Augusto; Raile, Vivian; Batistela, Rosangela Alice; Stella, Florindo; Bucken Gobbi, Lilian Teresa (Elsevier B.V., 2012)
The current study addressed the role of visual information in the control of locomotion in people with Parkinson's disease. Twelve healthy individuals and 12 mild to moderate Parkinson's disease patients were examined while walking at self-selected velocities, under three visual sampling conditions: dynamic (normal lighting), static (static visual samples) and voluntary visual sampling. Subjects wore liquid crystal glasses for visual manipulation. Outcome measures included spatial-temporal parameters, braking and propulsive impulses, number of samples and total duration of voluntary visual samples. Interaction between groups and visual conditions was not observed for kinematic parameters or braking and propulsive impulses. There were no significant differences between groups for voluntary visual sampling variables. These findings suggest that the visual control of locomotion in Parkinson's disease patients was similar to that observed in controls. Furthermore, Parkinson's disease patients were not more dependent on visual information than healthy individuals for the locomotion control. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Parkinson's disease; Motor control; Optic flow; Gait